Increased aeration efficiency of high-head conduit flow systems - Unsal, Mehmet; Baylar, Ahmet; Tugal, Mehmet; Ozkan, Fahri (Int Assoc Hydraulic Research, 2008)
Dissolved oxygen is the amount of oxygen dissolved in water corresponding to an important water quality parameter in rivers, streams, and lakes. If the gate of a high-head outlet conduit is partly opened, a negative pressure draws the air through the air vent. Air entrained into the water is instantly forced downstream in the form of small air bubbles. The solution of oxygen into the water results from the air entrainment downstream of the high-head conduit. Moreover, high pressure in high-head conduit flow systems also facilitates the solution of oxygen into the water. Herein, an experimental study was conducted to investigate the aeration efficiency of high-head conduit flow systems. The results indicate that high-head conduit flow systems are effective for oxygen transfer. Moreover, a regression equation was obtained relating the aeration efficiency to the characteristic Froude number.
Keywords: Aeration efficiency; air entrainment; conduit; high-head flow; oxygen transfer